Quality competition versus price competition goods: An empirical classification - Richard E. Baldwin; Tadashi Ito (Graduate Institute of International and Development Studies, 2008)
Based on the recent trade models of the Heterogeneous Firms Trade (HFT) model and the Quality Heterogeneous Firms Trade (QHFT) model, we classify export goods (at the HS 6-digit level of disaggregation) by quality and price competition. We find a high proportions of quality-competition goods for the major EU countries and lower proportions for Canada, Australia and China. However, the overlap of these quality-competition goods is not large, which suggests that characteristics of export goods are substantially different across countries at the same HS 6-digit code.
Keywords: F14; 330; quality vs price competition; heterogeneous firms trade model; Güter; Export; Wettbewerb; Preis; Produktqualität; Messung; Industriestaaten